Diabetes, Glycemic Control, and Risk of Infection Morbidity and Mortality: A Cohort Study. (16th August 2019) - Chang, Chia-Hsuin; Wang, Jiun-Ling; Wu, Li-Chiu; Chuang, Lee-Ming; Lin, Hsien-Ho
Abstract: Objective: Diabetic patients have an elevated risk of infection, but the optimal level of glycemic control with the lowest infection risk remains unclear, especially among the elderly. We aimed to investigate the relation between fasting plasma glucose (FPG) level and risk of infection-related morbidity and mortality. Method: The participants were from a community-based health screening program in northern Taiwan during 2005–2008 (n = 118 645) and were followed up until 2014. Incidence of hospitalization for infection and infection-related death was ascertained from the National Health Insurance Database and National Death Registry. Cox proportional hazards regression modelling was used to estimate the hazard ratio (HR) between FPG and risk of infection. Results: During a median follow-up of 8.1 years, the incidence rate of hospitalization for any infection was 36.33 and 14.26 per 1000 person-years among diabetics and nondiabetics, respectively, in the total study population, but increased to 70.02 and 45.21 per 1000 person-years, respectively, in the elderly. In the Cox regression analysis, the adjusted HR comparing diabetics to nondiabetics was 1.59 (95% confidence interval [CI], 1.52–1.67) for any hospitalization for infection and 1.71 (95% CI, 1.36–2.16) for infection-related mortality. The hazard for infection morbidity and mortality was higher at both extremes (<90 and >200 mg/dl) of FPG. The excess risk associated with FPG ≤ 90 mg/dl was attenuated after controlling for multiple comorbidities. Conclusions: Poor glycemic control (FPG > 200 mg/dl) was associated with a higher risk of infection-related morbidity and mortality, especially in the elderly population where the baseline infection risk was high. Abstract : Few studies have longitudinally assessed the association between glycemic control and risk of infection mortality. In this study, a U-shaped relation between fasting plasma glucose level and infection-related outcome was observed. After controlling for multiple comorbidities, the increased risk among those with a low fasting glucose level were attenuated, suggesting that comorbidities may play a role in the excess risk associated with low fasting plasma glucose level, in particular among elderly diabetic patients.